Dust and gas in luminous proto-cluster galaxies at z=4.05: the case for different cosmic dust evolution in normal and starburst galaxies - Tan, Q; Daddi, E; Magdis, G; Pannella, M; Sargent, M; Riechers, D; Bethermin, M; Bournaud, F; Carilli, C; da Cunha, E; Dannerbauer, H; Dickinson, M; et al. (EDP Sciences, 2014)
We measure the dust and gas content of the three submillimeter galaxies (SMGs) in the GN20 proto-cluster at z = 4.05 using new IRAM Plateau de Bure interferometer (PdBI) CO(4-3) and 1.2-3.3 mm continuum observations. All these three SMGs are heavily dust obscured, with UV-based star formation rate (SFR) estimates significantly smaller than the ones derived from the bolometric infrared (IR), consistent with the spatial offsets revealed by HST and CO imaging. Based also on evaluations of the specific SFR, CO-to-H2conversion factor and gas depletion timescale, we classify all the three galaxies as starbursts (SBs), although with a lower confidence for GN20.2b that might be a later stage merging event. We place our measurements in the context of the evolutionary properties of main sequence (MS) and SB galaxies. ULIRGs have 3-5 times larger L'CO/Mdustand Mdust/M ratios than z = 0 MS galaxies, but by z ∼ 2 the difference appears to be blurred, probably due to differential metallicity evolution. SB galaxies appear to slowly evolve in their L'CO/Mdustand Mdust/M ratios all the way to z> 6 (consistent with rapid enrichment of SB events), while MS galaxies rapidly increase in Mdust/M from z = 0 to 2 (due to gas fraction increase, compensated by a decrease of metallicities). While no IR/submm continuum detection is available for indisputably normal massive galaxies at z> 2.5, we show that if metallicity indeed decrease rapidly for these systems at z> 3 as claimed in the literature, we should expect a strong decrease of their Mdust/M, consistent with recent PdBI and ALMA upper limits. We conclude that the Mdust/M ratio could be a powerful tool for distinguishing starbursts from normal galaxies at z> 4.